2019
DOI: 10.1002/aic.16893
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of liquid–liquid mass transfer performance in a novel pore‐array intensified tube‐in‐tube microchannel

Abstract: Liquid–liquid mass transfer performance of a novel pore‐array intensified tube‐in‐tube microchannel (PA‐TMC) was investigated with the water‐benzoic acid‐kerosene system. Both mass transfer efficiency (E) and volumetric mass transfer coefficient (K La) are found to increase simultaneously with the flow rate, but decrease with total number of pores and rows. However, E increases but K La decreases with the annular length. In particular, the pore size shows an optimal value at 0.3 mm due to the interplay problem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 19 publications
(4 citation statements)
references
References 54 publications
0
4
0
Order By: Relevance
“…Porous materials are used in various applications, including batteries, separators, medicine applications, and organic syntheses [1][2][3][4][5][6][7][8]. They have been mainly used as watertreatment membranes, gas-separation membranes, battery separators, and catalysts of various syntheses [9][10][11][12][13][14][15][16].…”
Section: Introductionmentioning
confidence: 99%
“…Porous materials are used in various applications, including batteries, separators, medicine applications, and organic syntheses [1][2][3][4][5][6][7][8]. They have been mainly used as watertreatment membranes, gas-separation membranes, battery separators, and catalysts of various syntheses [9][10][11][12][13][14][15][16].…”
Section: Introductionmentioning
confidence: 99%
“…Porous polymeric materials are substances that have nano-sized pores, which are actively used in adsorbents, catalysts, water treatment and gas separation membranes, and electrical and chemical materials. (Li et al 2019;Otaru et al 2019;Xu et al 2018;Notario et al 2016;Rashidi et al 2018;Samanta et al 2019;Sun et al 2016;Huang 2016) The separation process using porous polymer membranes is seeing a rapid growth in a variety of applications, despite its short history compared to other process technologies. This is because porous membranes have various advantages: easy to use, relatively low cost and space, environmental friendliness, and convenience of post-processing.…”
Section: Introductionmentioning
confidence: 99%
“…It was found that the number of dispersing elements was essential for the liquid–liquid dispersion and a dynamics mechanism of droplets was proposed. Li et al 11 characterized a liquid–liquid mass transfer performance in a novel pore‐array intensified tube‐in‐tube microchannel. It was found that the overall mass transfer coefficient and throughput of the reactor were higher than those of other types of contactors.…”
Section: Introductionmentioning
confidence: 99%